Referenca besede buča v Dalmatinovi Bibliji - Sirk, Stanislava (Slavistična revija, 2001)
The article treats the difference of the word buča in Dalmatin's Bible (1584). According to Bezlaj (1976) the word refers to Cucurbita pepo, but if the plant is viewed from botanical point of view and the word buča examined in Slovene dictionaries and some land registers, one can conclude that Dalmatin's buča was not Cucurbita pepo, but Lagenaria ciseraria. The word Buča as a plant name would have perhaps even disappeared where it not for a fortunate coincidence, i.e., the original semantic field of Lagenaria siceraria, which was beginning to fade, was replaced by Cucurbita pepo. The replacement was so consistent that with the entry buča neither Bezlaj nor Snoj (1997) in their etymological dictionaries mention Lagenaria siceraria.
Keywords: Bible; Dalmatin, Jurij, 1547-1589; onomastics; onomastika; rastlinska imena; Slovene; slovenščina; sveto pismo